1941
DOI: 10.1007/bf01344190
|View full text |Cite
|
Sign up to set email alerts
|

Berechnung mehrerer Terme der Na- und K-Atome und des Grundtermes der A1+- und A1++-Ionen

Abstract: Es werden mat der yon P. Gomb~s entwickelten Ngherungsmethode:) die 3 S-, 4S-, 3P-, 4P-, 3D-Terme des Na-Atoms, die 4S-, 4P-, 3D-, 4F-, 5 G-Terme des K-Atoms und der Grundterm der AI+-und A1 + +-Ionen mit den entsprechenden Eigenfunktionen bereehnet. Die Resultate, welehe mit den empirischen gut fibereinstimmen, werden diskutiert.Es wird die yon P. Gomb~s zur Bestimmung der Terme und Eigenfunktionen entwickelte N~herungsmethode:) auf die Atome und Ionen Na, K, A1 + und A1 ++ angewendet. Beziiglich der Methode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1949
1949
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We then considered the second term of Equation (1) as a perturbation and found that it contributes + 0.525 eV, which leads to a total energy of -3.346 eV. This now explains why Kozma and Konya [4] found -3.696 eV for the (4s) ground state, while our variational calculation based on the full expression in Equation (1) yielded only -3.476 eV.…”
Section: Csavinszky a N D Hucekmentioning
confidence: 85%
See 3 more Smart Citations
“…We then considered the second term of Equation (1) as a perturbation and found that it contributes + 0.525 eV, which leads to a total energy of -3.346 eV. This now explains why Kozma and Konya [4] found -3.696 eV for the (4s) ground state, while our variational calculation based on the full expression in Equation (1) yielded only -3.476 eV.…”
Section: Csavinszky a N D Hucekmentioning
confidence: 85%
“…The quantity given in Equation (1) differs from that in the earlier formulation [3] of the pseudo potential (on which [4] and [5] are based) by the appearance of the second term in the square brackets. We have found that the contribution to the energy from this term is considerable and, for this reason, used Equation (1) in its entirety.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations